(untitled) (Bangladesh Journal of Botany, 2020)
A differential response to terminal heat stress was observed on enzymatic and non-enzymatic components of antioxidant system of two thermo-tolerant genotypes viz., RGN-368 & RH-1566 and two thermo-sensitive genotypes viz., RH-1134 & RH-0749 in leaves of Indian mustard. The antioxidative enzymes viz., superoxide dismutase, peroxidase, catalase, ascorbate peroxidase and glutathione reductase showed higher activity in leaves of two thermo-tolerant genotypes as compared to thermo-sensitive. Terminal heat stress resulted in concomitant increase in non-enzymatic components like carotenoids, ascorbic acid and proline in all the genotypes but maximum increase was observed in thermo-tolerant genotypes. A remarkable accumulation was observed in oxidative stress indicators i.e., malondialdehyde, hydrogen peroxide and electrolyte leakage in all the genotypes, whereas, significant increase was observed in thermo-sensitive genotypes as compared to thermo-tolerant. It is inferred that leaves of thermo-tolerant genotypes tend to attain greater capacity to perform reaction of antioxidative pathway under the condition of terminal heat stress to combat thermo-induced oxidative stress.